2017
DOI: 10.1108/jmtm-09-2016-0123
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management practices and performance

Abstract: Purpose The purpose of this paper is to investigate the impact of organizational size on adoption of green supply chain management (GSCM) practices for the Indian industry. It also evaluates the impact of GSCM practices on organizational performance. Design/methodology/approach This study aims to empirically test the GSCM model to investigate the present orientation of the Indian industry toward GSCM practices using a pre-tested structured questionnaire. The statistical inferences were drawn using the data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
126
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 72 publications
6
126
0
Order By: Relevance
“…However, here again, the previous literature is insufficiently clear: while some studies (e.g. Vijayvargy et al, 2017) report higher environmental performance benefits for large firms (vis-à-vis smaller ones) from GSCP implementation, the converse is noted by others such as Grant et al (2002). This is also the case for long-term economic (or organizational) performance benefits from GSCP implementation; the few studies that have been done have reported both greater (e.g.…”
Section: Introductionmentioning
confidence: 79%
“…However, here again, the previous literature is insufficiently clear: while some studies (e.g. Vijayvargy et al, 2017) report higher environmental performance benefits for large firms (vis-à-vis smaller ones) from GSCP implementation, the converse is noted by others such as Grant et al (2002). This is also the case for long-term economic (or organizational) performance benefits from GSCP implementation; the few studies that have been done have reported both greater (e.g.…”
Section: Introductionmentioning
confidence: 79%
“…Qinghua Zhu, Tian, and Sarkis (2012) highlight that top management initiative is most important to adopt GSCM practices in the Chinese firm. Top management perception likely influences their behavior to sustainability practice (Vijayvargy, Thakkar, & Agarwal, 2017;Qinghua Zhu, Sarkis, & Geng, 2005). The firm with a higher environmental management system, compliance, and auditing practices can lessen the environmental impact of their manufacturing (Qinghua .…”
Section: Green Supply Chain Management Practicesmentioning
confidence: 99%
“…ED emphasizes to design of the product those are manufactured considering the product lifecycle analysis to minimize the environmental impact. Many researchers focused on ED as a GSCM practice which incorporates the environmental aspects from product idea to usage and finally disposal (Vanalle et al, 2017;Vijayvargy et al, 2017;Qinghua Zhu et al, 2007).…”
Section: Green Supply Chain Management Practicesmentioning
confidence: 99%
See 2 more Smart Citations